"Because That's the Culture": Providers' Perspectives on the Mental Health of Latino Immigrant Youth. (October 2018) - Olcoń, Katarzyna; Gulbas, Lauren E.
Immigrant youth experience a combination of stressors, such as isolation and discrimination, that put them at a greater risk for negative mental health outcomes. Relying on interviews with 24 service providers who work with Latino immigrant youth, this article examines how they construct and intervene in the worlds of immigrant youth to improve youth's mental health outcomes. Inductive thematic analysis revealed providers' reliance on cultural interpretations of the psychosocial circumstances facing immigrant youth. Providers alternated between drawing on discourses that reproduced stereotypes, assumptions, and biases, while simultaneously striving to transcend sociocultural differences to focus on the lived experiences of their clients. Although providers acknowledged the importance of structural barriers, such as poverty and discrimination, they "bracketed" these issues when recommending interventions. The article highlights that as cultural competence increasingly becomes part of social services, this professional discourse may distract providers' attention from more relevant targets of intervention.